Perceptions of mental health nurses about psychosocial management of depression in adolescents, North West province, South Africa - Precious C. Chukwuere; Leepile A. Sehularo; Mofatiki E. Manyedi (AOSIS, 2021)
Background: Depression in adolescents is a multifactorial global public health concern, with devastating consequences on the sufferer. The prevalence of depression amongst this age group is on the rise, and thus there is the need for greater attention. Aim: To explore and describe the perceptions of mental health nurses regarding the psychosocial management of depression in adolescents in North West province, South Africa. Setting: The study was conducted in two mental healthcare institutions and two mental healthcare units within two general hospitals in North West province, South Africa. Method: A qualitative, explorative, descriptive and contextual research design was used in conducting this study. Data were collected through focus group discussions from four groups of mental health nurses from each of the mental healthcare institutions and mental healthcare units with 18 mental health nurses. Data were analysed using Tesch's open coding method. Results: Two themes emerged from the study: comprehensive psychosocial management and involvement of different stakeholders. Conclusion: The findings revealed clear psychosocial management for depression in adolescents. Adopting the findings of this study could improve depressive symptoms and curtail the prevalence of depression amongst adolescents in the North West province, South Africa.